Sage ACT! 2011 dashboard and report cookbook : over 65 simple and incredibly effective recipes for creating and customizing exciting Dashboards and Reports from your ACT! data /: over 65 simple and incredibly effective recipes for creating and customizing exciting Dashboards and Reports from your ACT! data. (2011) - Unknown
No abstract available